O número graduado de Betti - Rezende, José Éverton de Jesus (2013)
This dissertation aims at a detailed study of the Hilbert function and graded Betti number and the statements of some theorems that relate these two theories. We will also a brief overview on free resolutions and minimal simplicial complex to demonstrate the theorem of Bayer, Sturmfels and Peeva and then, we will conclude with the following result: given an ideal J we will display a set X P2 such that the minimal resolution the ideal of de nition of X has the same Betti diagram of the minimal resolution of J.